Biochemical Oxygen Demand Modeling in Waste Stabilization Pond Model - Siharath, Phoummixay; Vilaychaleun, Somchay; Thammathevo, Khampasith; Kannitha, Soulyphan; Sonemanivong, Chankhachone; Siharath, Phaiphana; Singharaj, Sangkhom; Saktikoun, Thongsalak; Keokhamphui, Keoduangchai (Darul Yasin Al Sys, 2024)
The objective of the study is to optimize the kinetic reaction value and model the Biochemical Oxygen Demand (BOD5) on remaining and removal in the waste stabilization pond model, therefore, the waste stabilization pond system includes an anaerobic, facultative and maturation ponds, the study are employed the initial concentration of BOD5 (44.67±6.79 mg/l) from the wastewater sources at Huakhua village, Xaysettha District, Vientiane Capital, additionally, the evaluation are conducted in 3 hydraulic schemes that includes: plug flow, complete mix(single cell) and complete mixed (equal cells in series), consequently, according to the results found that: kinetic reaction values is 0.49 d-1 and the coefficient of determination (R2) are 0.99, 0.95 and 0.98, respectively.